Perl black book - Steven Holzner (Dreamtech Press, 2010)
The most comprehensive Perl book in the market - with more than 1000 examples and three bonus chapters in the CD - ROM - the new editions of the best selling Perl Black Book covers Perl 5.6 from basic syntax to the most advanced Internet Programming. Three new chapters have been added to this second edition covering XML with DOM, SAX, CGI, SOAP, and WML. From Perl essentials to working with XML and WML, from creating guest books to writing bi-directional Internet socket programs to implementing shopping cart programs, this book covers as much Perl as any two books, and includes hundreds of pages on CGI Programming. Plus, every topic is illustrated with at least one fully functional working example